2001
DOI: 10.1053/jhep.2001.28708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of naturally occurring surface gene variants of hepatitis B virus in nonimmunized surface antigen-negative Chinese carriers

Abstract: Previous studies have suggested that hepatitis B virus (HBV) variants may account for the presence of HBV DNA in hepatitis B surface antigen (HBsAg)-negative patients (occult HBV infection). However, it is not known how widespread these variants are and how they influence the course of liver disease. To determine the prevalence of variants within the major hydrophilic region (MHR) of HBsAg, we investigated 2,565 subjects, including subjects with chronic hepatitis, cryptogenic cirrhosis, hemodialysis patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
164
4
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(183 citation statements)
references
References 52 publications
12
164
4
3
Order By: Relevance
“…In this study, although the frequently emerged variant G145R was not found, some other variants showing single amino acid substitution patterns of the 'a' determinant, which had been reported previously, were observed [29][30][31]. All isolates showing T123A and M133L substitutions, together with 4 of the T143M isolates, were obtained from isolated anti-HBc samples; while one of the T143M isolates was found in samples with anti-HBc and anti-HBs.…”
Section: Lp V Cp L I Pgs S T T S T Gp Ck Tc T T Paqgtsm Fp S Ccc T Kpsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, although the frequently emerged variant G145R was not found, some other variants showing single amino acid substitution patterns of the 'a' determinant, which had been reported previously, were observed [29][30][31]. All isolates showing T123A and M133L substitutions, together with 4 of the T143M isolates, were obtained from isolated anti-HBc samples; while one of the T143M isolates was found in samples with anti-HBc and anti-HBs.…”
Section: Lp V Cp L I Pgs S T T S T Gp Ck Tc T T Paqgtsm Fp S Ccc T Kpsupporting
confidence: 58%
“…While M133L substitution did not show significant alteration, both T123A and T143M mutations demonstrated results that should be taken into account; pattern T123A resided in close proximity to the cysteine residues at 121 and 124, which form disulfide bonds that are important for maintaining the 'a' determinant's conformation [30,33]. This close proximity substitution might cause alteration in the steric hindrance that would disturb the disulfide bonds, and hence might affect HBsAg conformation and its detection.…”
Section: Lp V Cp L I Pgs S T T S T Gp Ck Tc T T Paqgtsm Fp S Ccc T Kpmentioning
confidence: 90%
“…Substitutions at positions 122 and 160 have been identified in different cases and were found to be associated with immune escape or diagnostic failure. Substitutions at the position 122 occurred in chronically HBV-infected patients that were tested negative for HBsAg (Alexopoulou et al, 2004;Grethe et al, 1998;Hou et al, 2001;Weinberger et al, 2000). Tian et al (2007) further confirmed that the K122I substitution had a major influence on HBsAg antigenicity.…”
Section: Introductionmentioning
confidence: 95%
“…Mutant HBV strains displaying amino-acid substitutions in the region known as the 'a' determinant of HBsAg can modify the antigenicity of the protein and may impair virion secretion and HBsAg formation [Chen et al, 2003;Shizuma et al, 2003;Khan et al, 2004], as well as the detection of the antigen by the routine diagnostic tests (Table I) [Wallace et al, 1994;Carman, 1997;Carman et al, 1997;Ireland et al, 2000;Hou et al, 2001;Allain, 2004]. Such mutants have also been reported in association with escape from vaccineinduced immunity [Oon et al, 1995;Carman, 1997;Ho et al, 1998;Chong-Jin et al, 1999;He et al, 2001;Lee et al, 2001;Seddigh-Tonekaboni et al, 2001] and with failures of therapy with specific immunoglobulin in newborns from carrier women and in liver-transplant recipients [Harrison et al, 1994;Oon et al, 1996Oon et al, , 2002Brind et al, 1997;Carman, 1997;Ngui et al, 1997;Protzer-Knolle et al, 1998;Santantonio et al, 1999;Roznovsky et al, 2000;Liu et al, 2002].…”
Section: Introductionmentioning
confidence: 99%